Separation Study of Titanomagnetite Fe3-xTixO4 from Natural Sand at Indramayu, West Java - Sunaryo, Sunaryo; Sugihartono, Iwan (UI Scholars Hub, 2010)
Separation Study of Titanomagnetite Fe3-xTixO4 from Natural Sand at Indramayu, West Java. Titanomagnetite FeTiO4 has been obtained from metal sand which is separated from natural sand at Indramayu using magnetic separator with the magnetic field 0,3 Tesla. This method can improve titanomagnetite content from 32% to 63,6%. According to X-ray diffractometer (XRD) and data processing by general structure analyses system (GSAS) with χ2= 1,454 and Wrp = 0,1142 as correction factor of the peak to peak intensities, we conclude that χ2 about 0 and Wrp aproximately 10%. It indicates the datas with the error merely 0,1 can be accepted. Furthermore, HCl 32% and NH4OH 25% were added into separation result in order to increase titanomagnetite content. While X-ray flouresence (XRF) analyses shows weight fraction of titanomagnetite increase up to 100%.